Customer expectations towards semi-detached and bungalow house in Bukit Indah (Johor) Sdn Bhd / Mastura Ayob - Ayob, Mastura (2004)
Bukit Indah (Johor) Sdn Bhd is a subsidiaries of S P Setia Bhd which it main activities is property development, building construction and wood based manufacturing. BIJ will soon to launch it new house product, which is double storey semi-detached house and in progress to confirm and prove design for bungalow house. To make the product be accepted to the market BIJ focus on what are the customer expectation toward bungalow and semi-detached house in order to create satisfaction and demand. The purpose of this research is to identify what are the customer expectation toward bungalow and semi-detached house. This research however discovered the main expectation that is important aspect for BIJ in focusing their target. This research involved 60 respondents, which is the population in BIJ, customer of BIJ itself and the customer of BIJ club. The respondent has been choosing randomly. Several techniques used to obtain information from respondent that is distributed questionnaires and personal interview. In findings and interpretation of data three methods used. Those include frequencies to know quantity of respondents that frequently gain for given factors, cross tabulation method used in order to know the correlation between one factors to another factors, and last method used was chi-square method to measure the relationship between the factors and hypotheses.